Hubungan Kunjungan Antenatal Care (ANC) dengan Kesiapan Persalinan pada Ibu Hamil Trimester III di Puskesmas Srandakan Bantul - Difa Oktafiana; Diyah Paramita Nugraha; Nastiti Mangenjali (Jurnal Medika Cendikia, 2017)
The ANC visit aims to keep healthy mothers during pregnancy, childbirth, and childbirth as well as babies who are born healthy seek to monitor the possibility of a high risk pregnancy and childbirth planning and preparedness so as to help reduce the number of maternal morbidity and mortality as well as the fetus. From the preliminary study conducted by researchers at the Health Office in Bantul highest ANC visit heal th centers located in Bantul Srandakan as much as 98.7%. Objective this research to identify whether there is a correlation ANC to the readiness of labor in the third trimester pregnant women at Srandakan Bantul Primary Health Care. Methods this research is a quantitative research, using observational analytic design with cross sectional approach. A sample of 46 respondents with a total sampling technique. The research instrument used questionnaires and checklists. Data analysis using Chi-square test using SPSS 17. Results, the ANC visits regularly and is ready to perform the readiness of labor as many as 37 people (80.4%). Based on the results of Chi-Square Test values obtained P value of 0.003 for x2 count (8.596)> x2 table (3.841) and p <0.05, then Ho is rejected or accepted Ha. This means that there is a relationship with the ANC readiness of labor in pregnant women TM III in Srandakan Bantul Primary Health Care.